2015
DOI: 10.1038/labinvest.2014.142
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Notch signaling reverses the Th17/Treg imbalance in cells from patients with immune thrombocytopenia

Abstract: T helper 17 (Th17) cells and regulatory T (Treg) cells, along with Th1 and Th2 cells, may contribute to the development of immune thrombocytopenia (ITP). The imbalance of Th17/Treg toward Th17 cells has been shown to play a pivotal role in the peripheral immune response. Notch signaling has been implicated in peripheral T-cell activation and effector cell differentiation. However, the role of Th17/Treg in the pathogenesis of ITP and the effect of Notch signaling on Th17/Treg imbalances remain largely elusive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Lv et al reported that miR141-CXCL1-CXCR2 signal-induced Treg recruitment could regulate the metastasis and survival rate of non-small cell lung cancer [11] ; Dong et al found that, in patients with rheumatoid arthritis, there was the correlation between the reduced expression of miR-21 and the imbalance of Th17 and Treg cells [12] . Though this study confirmed the positive correlation between the up-regulated expression of miR-21 and the ratio of Th17/Treg, it is still essential to study the specific regulatory mechanism of molecular biology, in order to provide the new target spots for the diagnosis and treatment of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Lv et al reported that miR141-CXCL1-CXCR2 signal-induced Treg recruitment could regulate the metastasis and survival rate of non-small cell lung cancer [11] ; Dong et al found that, in patients with rheumatoid arthritis, there was the correlation between the reduced expression of miR-21 and the imbalance of Th17 and Treg cells [12] . Though this study confirmed the positive correlation between the up-regulated expression of miR-21 and the ratio of Th17/Treg, it is still essential to study the specific regulatory mechanism of molecular biology, in order to provide the new target spots for the diagnosis and treatment of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…13 With regard to the role of Notch signalling in Treg cells, contradictory results are present in previous studies, including either positive or negative effects on Treg cell homeostasis and function. [14][15][16] However, the exact role of Notch signalling in the modulation of uveitic Treg cells, especially infiltrating Treg cells in uveitic eyes, has not been specified.…”
Section: Introductionmentioning
confidence: 99%
“…Conversion of T reg to Th17 cells is regulated partly by epigenetic modifications of transcription factors and signature cytokines [15,33]. The T reg /Th17 ratio may be a useful marker for assessing the severity of diseases in ITP [34]. Interestingly, we found that the CCR6 + Th17/ CCR6 + T reg ratio was higher in ITP patients compared with healthy controls and correlated with the response of treatment, suggesting that the CCR6 + Th17/CCR6 + T reg imbalance might be involved in the pathogenesis of ITP.…”
Section: Discussionmentioning
confidence: 99%